Development of photopolymerized fluorescence sensor for glucose analysis - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (ELSEVIER SCIENCE SA, 2013)
The sensing membrane was prepared by photopolymerization of 4-vinylphenylboronicacid (VPBA), hydroxyethylmethacrylate (HEMA) and poly(ethylene glycol) diacrylate (PEG-DA). The membran is capable of determining glucose between 2.78 x 10(-4) mM and 5.56 x 10(-3) mM with a limit of detection of 0.89 x 10(-5) mM, and limit of quantification 3.17 x 10(-3) mM (n = 7). It can be completely regenerated by using distilled water. The sensor performance characteristics such as response time, dynamic working range and sensitivity were reported. The proposed sensor was then applied successfully for the determination of glucose in blood samples. The optical sensor was stable, cost effective, easy to prepare, rapid and simple for the determination of glucose. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Glucose analysis; Optical sensor; Fluorescence; Membrane; UV-curing; IMPRINTED POLYMERS; SACCHARIDES; SEPARATION; SUGARS; ARRAY